PERAN DAYA SAING DALAM MEMEDIASI PENGARUH KEPEMIMPINAN DAN KINERJA INDUSTRI KREATIF - Nurlina Nurlina (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to analyze: (1) to analyze the influence of leadership on the performance of the creative industry, (2) to analyze the influence of leadership on competitiveness, (3) to analyze the effect of competitiveness on the performance of creative industries, (4) to analyze the role of competitiveness in mediating the influence of leadership. on the performance of the creative industry in Makassar City. This research is a quantitative research. The population of this research is all creative industry players in the city of Makassar, consisting of 258 culinary industry types, 71 advertising industry types, and 19 application and game industry types. So the total population is 342 creative industry players. The method used in sampling was simple random sampling with accidential random sampling technique with a total sample of 100 respondents, while data analysis was performed using multiple linear regression analysis. The results: 1) Partially leadership, competitiveness has a positive and significant effect on the performance of the creative industry. 2) Partially, leadership has a positive and significant impact on competitiveness. 3) The role of competitiveness as a mediator in the relationship between leadership and the performance of the creative industry is still weak.